2016
DOI: 10.24191/jchs.v1i1.5852
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Depression and its Relationship to Health Related Quality of Life among Prostate Cancer Patients in Tertiary Centres, Kuala Lumpur

Abstract: Introduction: To determine the prevalence of depression and its relationship with health related quality of life among prostate cancer patients in tertiary medical centres, Kuala Lumpur. Methods: A hospital-based, cross-sectional study was conducted at the Surgical Clinic, University Malaya Medical Centre and Universiti Kebangsaan Malaysia Medical Centre over a period of fifteen months. Depression level was measured using Depression Anxiety Stress Scale (DASS-21) and the health related quality of life was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Though Rodi et al . [ 16 ] reported a weak significant negative correlation between anxiety score and total QOL among prostate cancer patients. Furthermore, in another study it has been demonstrated that stress can be negatively correlated with QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Though Rodi et al . [ 16 ] reported a weak significant negative correlation between anxiety score and total QOL among prostate cancer patients. Furthermore, in another study it has been demonstrated that stress can be negatively correlated with QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Besides using herbal intervention for cancer patients, a clinical trial using the Applied Progressive Muscle Relaxation Training (APMRT) was conducted (Isa et al, 2013). Overall, there was a significant change over time in the overall QOL of the cancer patients.…”
Section: Interventions and Quality Of Lifementioning
confidence: 99%